Postural stability and plantar pressure parameters in healthy subjects: variability, correlation analysis and differences under open and closed eye conditions - De Blasiis, P.; Caravaggi, P.; Fullin, A.; Leardini, A.; Lucariello, A.; Perna, A.; Guerra, G.; De Luca, A. (Frontiers in Bioengineering and Biotechnology, 2023)
Introduction: The “postural control system” acts through biomechanical strategies and functional neuromuscular adaptations to maintain body balance under static and dynamic conditions. Postural stability and body weight distribution can be affected by external sensory inputs, such as different visual stimuli. Little information is available about the influence of visual receptors on stabilometric and plantar pressure parameters. The aim of this study was to analyze variability, correlations, and changes in these parameters under open- (OE) and closed-eye (CE) conditions. Methods: A total of 31 stabilometric and plantar pressure parameters were acquired in 20 young and healthy adults during baropodometric examination performed in bipedal standing under both visual conditions. Variability of parameters was evaluated via the coefficient of variation, correlation analysis via Pearson’s R2, and statistical differences via the Wilcoxon test. Results: High intra-subject repeatability was found for all plantar pressure parameters and CoP-speed (CV < 40%) under OE and CE conditions, while CoP-sway area (CoPsa) and length surface function (LSF) showed larger variability (CV > 50%). Mean and peak pressures at midfoot and total foot loads showed the least number of significant correlations with other parameters under both visual conditions, whereas the arch-index and rearfoot loads showed the largest number of significant correlations. The limb side significantly affected most plantar pressure parameters. A trend of larger LSF and lower CoPsa and mean and peak pressures at the right forefoot was found under the CE condition. Discussion: The present study provides a deeper insight into the associations between postural stability and foot load. Interesting postural adaptations, particularly with respect to different visual stimuli, the effect of the dominant side, and the specific role of the midfoot in balance control were highlighted.